Pengaruh Kualitas Layanan terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Intervening (Studi pada Pelanggan Dunkin Donuts di Surabaya dan Sidoarjo) - Kiki Amelia Dewi (BISMA (Bisnis dan Manajemen), 2018)
The purpose of this study is to find out is there any influence of service quality on customer loyalty through customer satisfaction as intervening variable on customer Dunkin Donuts in Surabaya and Sidoarjo. This research using non-probability sampling with judgemental sampling as sampling category. This research take 220 people as a respondents of the sample object. The respondents of this research is the customer Dunkin 'Donuts men and women aged 18-50 years who have made a purchase and consume directly at the Dunkin' Donuts at least 2 times in the last 3 months. The instruments used is an observation, documentation, interview and questionnaire that analyzed using a Likert scale. Analysis of data using path analysis. The result of this research showed that there is any influence of service quality on customer loyalty through customer satisfaction as intervening variable.